Influence of taping on athletes` psychomotor possibilities in sprint - Vynohradov, V.; Lopatenko, H.; Biletska, V.; Trachuk, S.; Semenenko, V.; Kudria, M.; Shemchuk, V.; Napadij, A. (Journal of Human Sport & Exercise, 2022)
Sprint results are more often seen as deliberate practice model (DPM) effects. The performance is limited, as the goal is the same for every competition - to run as fast as possible. This requires a specific skill. The researches confirm that a prerequisite for elite sprinting is an exceptional speed to formal training; this exceptional ability is partially sprint-specific; many elite sprinters achieve the world-class status in less than 10 years, which suggests DPM (Michael, Lombardo, 2014). Introduce the technology of combining special exercises with kinesiotaping as a way to solve the motor task in the sprint - to run fast. In the training, the special exercises were used, the kinesiotaping was applied to enhance psychomotor skills and exacerbate the proprioceptive sensitivity of individual parts of the body. 10 qualified 21-24 year-old men-sprinters having 5-7 years of sprint training practice took part in sociological studies. A sequence of exercises is presented aimed at forming specialized sensations of `track feeling` in a track and field athlete-sprinter with the help of kinesiotaping. The possibility of forming the motor composition of a new skill for implementing the athletes` sprinting capabilities is revealed. The special exercises and kinesiotaping made it possible to solve motor tasks to form the basic skill of repulsion after giving back a track of any stiffness.